(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
The specialist performs a goal-oriented labor movement in the process of performing any work. For example, the structure of the production process in the construction industry includes a variety of works: earthworks (excavation and relocation of soil and stones, excavation and processing of soil, etc.), reinforced concrete works (installation of reinforced concrete structures etc.), stonework, wall installation, etc. The whole process of repairing or constructing complex structures or parts of them performed in the area of a construction site is called a construction process. For example, a bricklayer must make eye-catching movements to lay a brick on an outer pole, find the brick, extend his hand, pick up the brick, move it to the place of laying, and turn it.